Radde Khr̥shṭāna o dalilula Isalāma, ba, Khr̥shṭāna dharmera asāratā - Meherullah, Mohammad, 1861-1907 (Āñjumāne Tāmarinula Musalimina (Musalima Anuśīlana Saṃsthā), 1976)
A diatribe agains Christianity by a conservative Bengali Muslim religious leader.